Consumer Analysis Of Batik Pring Sedapur For Understanding Business Strategies - Wahyuni, Ajeng; Ainun Najib, M. Thoha (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to analyze the demographics and purchasing habits of Batik Pring Sedapur customers based on the customer perspective of the balanced scorecard (BSC). The analysis emphasizes two things: (1) customer core measurement consists of consumer satisfaction, loyalty, and acquisition, and (2) Customer values and profitability. Based on the purpose of the study, the data, and the respondents of the research, mixed methods is the suitable approach to use. The data will be analyzed using descriptive statistics to explain the respondent's answer, and the balanced scorecard (BSC) theory, especially from the customer perspective, will be used when presenting and analyzing the data. Batik Pring Sedapur Magetan offers opportunities in specialized product development for women, training and education in batik production, optimized digital marketing and social media, customer loyalty programs, enhanced customer engagement, expanded product selection, increased design customization services, batik village as cultural tourism, segmented targeting, emphasizing quality as a selling point, developing eco-friendly and sustainable batik, and international market appeal.